ソウテン ガタ リオメーター ノ カイハツ - 山岸, 久雄; ヤマギシ, ヒサオ; 菊池, 崇; キクチ, タカシ; Yamagishi, Hisao; Kikuchi, Takashi (1989)
P(論文) 半値幅13°のペンシル状アンテナビームを掃天する, 新型のリオメーターが開発され, 1985年2月南極昭和基地に設置された。このシステムは観測点の上空東西及び南北方向120kmの範囲内の電離層吸収を空間分解能10km, 時間分解能10秒で求めることができる。このシステムはまた常時, 磁南, 北, 西の天頂角30°方向, 及び天頂を向く四本のアンテナビームを備え, これらの方向については時間分解能0.25秒の高時間分解能観測を行うことができる。本観測システムにより, 従来の広ビームリオメーターでは検出が難しかった直径数10km以下の局在化された吸収現象や, 波長100km程度の小規模の脈動性吸収が伝搬する様子を観測することができた。また, オーロラ光学観測と本システムとの同時観測により光オーロラと電離層吸収の空間分布の差異が明らかにされた。 A new riometer system of high spatial resolution by means of a scanning narrow beam method is in operation at Syowa Station, Antarctica (69.0°S, 36.6°E, L=6.1) since February 1985. Ionospheric absorption of cosmic radio noise over Syowa Station within 120km in geomagnetic north-south and east-west directions, can be measured with a spatial resolution of 10km and a temporal resolution of 10s. The antenna system has four other fixed-direction beams pointing to the zenith and to the magnetic north, south and west with a zenith angle of 30°. Each signal from these fixed beams, constituting a separate riometer, is used for higher time resolution (0.25s) observation. This riometer system can discriminate a small-scale absorption region of a few tens of kilometers, which cannot be seen by a conventional broad beam riometer. This riometer system can also detect a drift velocity of pulsative absorption with a short wavelength of ∿100km. Comparing simultaneous observations of this riometer and a scanning photometer at Syowa Station, we found a considerable difference in spatial distribution between auroral absorption region and auroral emission region. departmental bulletin paper